Glycemic Control, Diabetes Complications and Their Determinants Among Ambulatory Diabetes Mellitus Patients in Southwest Ethiopia: A Prospective Cross-Sectional Study - YimamAhmed M (Diabetes, Metabolic Syndrome and Obesity : Targets and Therapy, 2020)
Mohammed YimamAhmed,1 Solomon Hambisa Ejigu,2 Ameha Zewudie Zeleke,2 Mohammed Yimam Hassen2 1Dubti General Hospital, Dubti, Afar Region, Ethiopia; 2Department of Pharmacy, College of Health Sciences, Mizan-Tepi University, Mizan-Aman, EthiopiaCorrespondence: Mohammed Yimam Hassen Email mohammedimam0094@gmail.comBackground: Over the past two decades, the prevalence of diabetes has increased faster in low- and middle-income countries than in high-income countries. Regardless of the instant growth in the prevalence of diabetes in Ethiopia, up-to-date data regarding glycemic control and related complications of diabetes is inadequate. This study aimed to identify glycemic control and chronic complications and their determinants among ambulatory diabetic patients at Mizan-Tepi University Teaching Hospital (MTUTH).Methods: We conducted facility-based cross-sectional study from February 25 to March 25, 2019, at Mizan-Tepi University Teaching Hospital. Patients’ demographic data, diabetes complications, and treatments were collected using pretested questionnaire and data abstraction format. Data was entered by using Epidata manager 4.0.2.101, and statistical analysis was done by SPSS version 21. Bivariate logistic regression was done to see the association between independent variables and glycemic control and complication. Multivariable logistic regression analyses using backward selection were done to identify the predictors of poor glycemic control and complication at a P-value of < 0.05.Results: One hundred ambulatory diabetic patients were included in this study. The mean duration of diabetes and the mean age of the participants were 3.95± 5.85 and 46.66± 15.53 years, respectively. About 71 (71%) of the studied diabetic patients had uncontrolled fasting blood glucose (FBG) level. More than half of the diabetic patients (59%) developed chronic complications of diabetes. Low medication adherence (adjusted odds ratio (AOR)=11.78, 95%CI: 1.09– 17.17) and inappropriate doses in the first, second, and third clinic visits (AOR=7.70, 95%CI: 1.79– 33.01; AOR=8.09, 95%CI: 1.90– 34.33; AOR=4.34, 95%CI: 1.09– 17.17), respectively, were independent predictors of uncontrolled FBG. No variable was found to be an independent predictor of chronic diabetic complication on multivariable logistic regression analyses.Conclusion: Poor glycemic control and diabetes complications among ambulatory diabetic patients were high. Low medication adherence and inappropriate doses in the first, second, and third clinic visits were independent predictors of poor glycemic control.Keywords: diabetes, glycemic control, complications, Ethiopia